Maximizing Growth and Yield of Garlic by using Different Sources and Dosages of Nitrogen and Chicken Manure on Andisol Soil - Dicky Nursasi; Achmad Fatchul Aziez; Tyas Sumarah Kurnia Dewi; Ongko Cahyono (Agricultural Science, 2023)
Low soil fertility is a limiting factor for crop production in general. Increasing the yield of garlic with balanced fertilization is an important key identified, also the right type and dose of fertilization is also a major problem. The purpose of this study was to determine the effect of inorganic fertilizer (nitrogen) and chicken manure doses on the growth and yield of garlic. The experimental design used in this research was a completely randomized design. The first factor was chicken manure, which consists of two levels, i.e., without chicken manure and 40 t/ha of chicken manure. The second factor was the dosage of N fertilizer which consists of twenty levels, ie, no fertilizer, urea with a dose of 50, 100, 150, 200, 250, 300, 350, 400. 450, 500 kg/ha, ZA with a dose of 50, 100, 150, 200, 250, 300, 350, 400. 450, 500 kg/ha. The results showed that the combination of urea fertilizer 500 kg/ha and chicken manure 40 tons/ha gave the highest yield of stored dry tubers and was significantly higher than control plots and other treatment combinations. Likewise other growth and yield parameters increased progressively. Therefore, it can be concluded that to increase the yield of garlic in the study area, 500 kg/ha of urea fertilizer and 40 tons/ha of chicken manure are needed. The recommendation is that on Andisol soil for garlic cultivation, it is better to use a combination of 500 kg/ha urea and 40 t/ha chicken manure.